Melatonin Improves Quality of Repeated-Poor and Frozen-Thawed Embryos in Human, a Prospective Clinical Trial - Bao, Zhongjian; Li, Guangdong; Wang, Rongxiang; Xue, Songguo; Zeng, Yong; Deng, Shoulong (Frontiers in Endocrinology, 2022)
Objective In this study, two experiments were performed to assess the effect and the role of melatonin on human in vitro embryo quality. Methods Experiment I: A total of 42 repeated-poor-quality-embryo patients were enrolled, with a total of 181 oocytes retrieval cycles. After IVF, for the same patient, the MT cycles group (10-7 M melatonin added to the culture medium; n=48) were compared with the previous non-MT cycles group (n=133), following by in vitro culture to blastocyst stage and embryo transfer. 31 patients were transplanted with 65 embryo transfer, including 24 MT embryo transfer, 41 non-MT embryo transfer. Cycle outcomes were compared between the two groups. Experiment II:A total of 143 supernumerary human cleavage-stage embryos (from non-repeated-poor-quality-embryo patients) vitrified on Day 3 after IVF were warmed and randomized into two groups: melatonin group (10-7 M melatonin added to the culture medium; n=71) and control group (n=72), and then cultured for 72 h. Rate of blastocyst and high-quality blastocyst, reactive oxygen species (ROS) levels of culture media as well as embryonic GPX1, CAT, Mn-SOD, Cu/Zn-SOD, BCL-2, BAX gene expression levels were analyzed. Results Experiment I: Results showed that the rate of Day 3 high-quality embryos (29.6% vs.19.5%) in the MT cycles group was significantly higher than that in the non-MT cycles group (P<0.05). The rate of available blastocysts (17.1% vs.12.7%) and clinical pregnancy rate (25.0% vs.17.1%) were in tendency higher in the group treated with melatonin (P>0.05). Experiment II:Results showed that the blastocyst rates in the melatonin administered group were significantly higher than in control group (42.25% vs.26.38%, P<0.05). There were no significant differences in high-quality blastocyst rates. In addition, quantitative PCR showed that the expression of CAT was significantly upregulated by melatonin treatment (P<0.05), while there were no significant differences in the expression of GPX1, Mn-SOD, Cu/Zn-SOD, BAX and BCL-2 gene as well as the levels of ROS. Conclusion These data showed that melatonin supplement in the culture medium will improve Day 3 high-quality embryos rate of repeated-poor-quality-embryo patients and improve blastocyst rate of vitrified-warmed cleavage-stage embryos, suggesting that melatonin intervention may provide a potential rescue strategy for IVF failures. Clinical Trial Registration identifier [ChiCTR2200059773].